SALAH PAHAM AL-MADAD DALAM AL-KUTŪB AL-SITTAH: - Nur Raihan; Ishak Suliaman (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2019)
The word Al-Madad in the Al-Kutub Al-Sittah is defined as help, that is, help given by Allah in the form of assistance from angels and help from living humans. However, the Habaib created a poem in the Qasidah